2005
DOI: 10.1203/00006450-200508000-00255
|View full text |Cite
|
Sign up to set email alerts
|

226 Evaluation of Developmental Centered Care in Spanish Neonatal Units

Abstract: Background: From clinical point of view it is important to detect all seizure activity in neonates. The cerebral function monitor (CFM) processes the electro encephalogram (EEG) into an amplitudeintegrated EEG (aEEG) signal that is relatively easy to read and interpret compared to the classical EEG. So far seizures were defined based on the visual interpretation of a typical pattern.Objective: The objective of this study is to create a program for automatic detection of seizures in neonatal aEEG signals, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a study on developmental care in the United Kingdom, although about 90% of NICUs reported an open visiting policy for parents and 80% of NICUs frequently used kangaroo care, only 64% of NICUs had developmental care personnel and only 57% had staff trained in developmental care . In several European countries, rates of breastfeeding and use of nonpharmacological analgesia for pain management varied greatly. Some NICUs have implemented procedures to control external stimuli (e.g., noise), but in some NICUs, staff have failed to support parents' involvement .…”
mentioning
confidence: 99%
“…In a study on developmental care in the United Kingdom, although about 90% of NICUs reported an open visiting policy for parents and 80% of NICUs frequently used kangaroo care, only 64% of NICUs had developmental care personnel and only 57% had staff trained in developmental care . In several European countries, rates of breastfeeding and use of nonpharmacological analgesia for pain management varied greatly. Some NICUs have implemented procedures to control external stimuli (e.g., noise), but in some NICUs, staff have failed to support parents' involvement .…”
mentioning
confidence: 99%
“…However, noise reduction measures remain consistently less well‐implemented, particularly among smaller units. Previous studies from Israel, Italy, the USA and Spain have reported a similar picture, despite staff awareness of the need to reduce the intensity and frequency of such environmental stimuli (2,16,17,23).…”
Section: Discussionmentioning
confidence: 72%
“…Regardless of the available evidence, appropriate systematic analgesia in common painful procedures in neonates is far from adequate 1 2…”
Section: Introductionmentioning
confidence: 99%